Clinical significance and biological role of L1 cell adhesion molecule in gastric cancer - Ichikawa, Takashi (Br J Cancer, 2019)
BACKGROUND: L1 cell adhesion molecule (L1CAM) is highly expressed in malignant tumours and might play a pivotal role in tumour progression. METHODS: We analysed by immunohistochemistry L1CAM protein expression in formalin-fixed, paraffin-embedded specimens from 309 GC patients. We performed propensity score matching (PSM) analysis to clarify the prognostic impact of L1CAM in GC patients. We evaluated L1CAM gene expression in fresh frozen specimens from another group of 131 GC patients to establish its clinical relevance. The effects of changes in L1CAM were investigated in vitro and in vivo. RESULTS: L1CAM was mainly expressed in tumour cells of GC tissues. Elevated L1CAM expression was an independent prognostic factor for overall and disease-free survival, and an independent risk factor for distant metastasis in GC patients. PSM analysis showed that high L1CAM expression was significantly associated with poor prognosis. L1CAM gene expression using fresh frozen specimens successfully validated all of these findings in an independent cohort. Inhibition of L1CAM suppressed cell proliferation, cycle progress, invasion, migration and anoikis resistance in GC cells. Furthermore, L1CAM inhibition suppressed the growth of peritoneal metastasis. CONCLUSION: L1CAM may serve as a feasible biomarker for identification of patients who have a high risk of recurrence of GC.